Intense gamma-ray source in the giant-dipole-resonance range driven by 10-TW laser pulses. - Giulietti, A; Bourgeois, N; Ceccotti, T; Davoine, X; Dobosz, S; D'Oliveira, P; Galimberti, M; Galy, J; Gamucci, A; Giulietti, D; Gizzi, L; Hamilton, D; et al. (2008)
A gamma-ray source with an intense component around the giant dipole resonance for photonuclear absorption has been obtained via bremsstrahlung of electron bunches driven by a 10-TW tabletop laser. 3D particle-in-cell simulation proves the achievement of a nonlinear regime leading to efficient acceleration of several sequential electron bunches per each laser pulse. The rate of the gamma-ray yield in the giant dipole resonance region (8